Database strategies : using Informix XPS and DB2 Universal Database - Ballard, Chuck (IBM redbooks., 2005)
The acquisition of Informix by IBM has provided the opportunity for Informix customers to consider new alternatives to further enrich their data management systems infrastructure. They can now more easily take advantage of available products, services, and capabilities as they grow and change. This IBM Redbooks publication focuses on strategies, techniques, capabilities, and considerations for using Informix Extended Parallel Server (XPS) and DB2 Universal Database (UDB). It provides detailed discussions and data to give a good understanding of the two products, their capabilities, and their similarities. XPS customers can choose to adopt a database strategy of coexistence or consider transitioning to DB2 UDB. The features and functionality of each DBMS are briefly described for a better understanding, in areas such as architecture, partitioning techniques, SQL considerations, configuration, indexing, data types, DML, and DDL. It also discusses products and tools to complement these database management systems. With this information, you can better decide which products satisfy your particular requirements, and better plan on how to achieve your objectives as you develop your database management system strategy. You will be better positioned to make informed decisions that can give you the best return on your DBMS investment.